2022
DOI: 10.1155/2022/8340450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thiol/Disulfide Homeostasis in Bronchiectasis

Abstract: Purpose. Thiols are sulfhydryl-containing organic compounds that have an important role in preventing cellular oxidative stress. This study compares the blood oxidative stress marker levels in bronchiectasis cases during their stable periods with healthy controls. Materials and Methods. Seventy-seven patients (49 patients with stable bronchiectasis/28 healthy controls), followed up by the chest disease clinic, were included in the study. Peripheral blood thiol-disulfide parameters (NT: native thiol (−SH); TT: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, Doğru et al obtained IMA values significantly higher in children with asthma attack and stable asthma compared to the control group, and IMA values were significantly higher in the patient group than the control group [ 16 ]. Özyurt et al reported a significant correlation between both thiol and IMA and bronchiectasis patients [ 17 ]. In our study, it is considered important that the patients were only hypercapnic, and they were not required to be in severe respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Doğru et al obtained IMA values significantly higher in children with asthma attack and stable asthma compared to the control group, and IMA values were significantly higher in the patient group than the control group [ 16 ]. Özyurt et al reported a significant correlation between both thiol and IMA and bronchiectasis patients [ 17 ]. In our study, it is considered important that the patients were only hypercapnic, and they were not required to be in severe respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…Thiols are responsible for the non-enzymatic removal of reactive oxygen molecules via non-enzymatic pathways [52]. These parameters are proposed as novel oxidative stress parameters in numerous conditions, such as cardiovascular, neurological, skin, and respiratory diseases [53][54][55][56]. Little is known about thiol/disulphide balance in schizophrenia.…”
Section: Plos Onementioning
confidence: 99%